Relevansi Pemikiran Ibnu Qayyim al-Jauziyah tentang Peranan Keyakinan Hakim dengan Sistem Pembuktian dalam Hukum Acara Pidana di Indonesia - Ilmiyah, Nailul (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2020)
The paper aims to expose the relevance of Ibn Qayyim al Jauziyah's thoughts in the role of judges' conviction with the evidence in the criminal procedural law system in Indonesia. The result shows that the function of the judge's conviction is considered a base or a consideration in deciding cases, in the sense that the belief is the act of the judge accompanying the emergence of evidence presented before the court. Ibn Qayyim al-Jauziyah argues that a judge's conviction is related to the broad knowledge of the law and the skill in reading the signs that arise in the case, it also considered a basic guideline for judges in deciding cases, in addition to legal provisions. The relevance of Ibn Qayyim al-Jauziyah's thoughts in criminal procedural law in Indonesia regarding the role of judges' belief is that both (according to Ibnu Qayyim and criminal procedural law in Indonesia) both emphasize that the conviction of judges has a very critical role in deciding cases.